MECHANICAL PROPERTIES CHARACTERIZATION OF RAT-TRAP BOND BRICK MASONRY - Samiullah; Ashraf, Mohammad; Fahim, Muhammad; Haris, Muhammad; Khan, Sajjad Wali; Khan, Wajid (Journal of Applied Engineering Science, 2022)
Brick masonry is one of the most popular building technique for residential buildings, especially in the developing countries. The two most common types of bonds adopted in brick masonry are English and Flemish. However, rat-trap bond is gaining popularity in South Asian countries like India, Pakistan, and Sri Lanka. It is a type of masonry bond in which shiners and rowlocks are laid on the edges such that the shiners have 1/3rd cavity between them resulting in cost reduction, dead load reduction, faster construction and thermal insulation, etc. This paper presents the results of an experimental investigation of rat-trap bond masonry for mechanical characterization. Four prism specimens were tested for compressive strength, four for diagonal strength, and twelve triplets were tested for shear strength. It was found that the mechanical properties of rat-trap masonry lie within the range of English bond masonry in Pakistan as determined by various researchers. In addition, the compressive strength and elastic modulus were found within the specified range of Building Code of Pakistan, while the shear modulus showed higher values.
Keywords: rat-trap bond, RTB, cost-effectiveness, compressive strength, diagonal strength mechanical properties, stress-strain relationship